Strongyloidiasis: Risk and Healthcare Access for Latin American Immigrants Living in the United States - Ostera, Graciela (Curr Trop Med Rep, 2016)
This commentary discusses our current understanding about Strongyloides stercoralis prevalence rates in the United States (USA) in the context of healthcare delivery to immigrants from Latin America. A literature search reveals that while prevalence rates in Latin American countries are not well documented, the rates in Latin American immigrants living in the USA are even less well known. This limited understanding compounds the health challenge facing immigrants who already have limited access to the healthcare system. To better address this problem, we suggest improved parasitological screening plus additional funding for free clinics.